Propriedades magnéticas do modelo de Hubbard em estruturas tipo FCC - Souza, Thiago Xavier Rocha de (2012)
The study about magnetic properties of strongly correlated electrons has been an problem of interest in physics by the great technological importance of various materials with this characteristic. A well-known theoretical approach, known as the Hubbard model, has been used in an attempt to describe such phenomena. This model considers the interactions and electron mobility in a simplified way for describing phenomena like itinerant magnetism and the metal-insulator transition. In this study were analyzed the thermodynamic clusters properties of structures with fcc lattice symmetry containing 4, 5, 6, 7 and 8 sites. An exact numerical diagonalization method was used, where the subspaces of the problem were separatly analyzed and put together on, which is a procedure that reduces the processing data time. In order to improve the diagram of quantum states also carried out a ground state analysis of the clusters, known in the literature and obtained from systems with 4, 5 and 6 sites. On this subject a new diagram was developed showing the quantum states transition using the Lanczos method, applied to clusters with 4 to 8 sites in this case. Finally, a comparison was made between the thermodynamic properties and the results found in the new quantum state diagram. The agreement between them is good.